Cody

# Problem 43596. Find the sum of the negative elements under the main diagonal.

Solution 1980125

Submitted on 17 Oct 2019 by Nikolaos Nikolaou
This solution is locked. To view this solution, you need to provide a solution of the same size or smaller.

### Test Suite

Test Status Code Input and Output
1   Pass
A = [1 2; -3 0]; y_correct = -3; assert(isequal(sumOfN(A),y_correct))

y = 1 0 -3 0 y = 0 0 -3 0 y = 0 0 -3 0 y = -3

2   Pass
A = ones(8); y_correct = 0; assert(isequal(sumOfN(A),y_correct))

y = 1 0 0 0 0 0 0 0 1 1 0 0 0 0 0 0 1 1 1 0 0 0 0 0 1 1 1 1 0 0 0 0 1 1 1 1 1 0 0 0 1 1 1 1 1 1 0 0 1 1 1 1 1 1 1 0 1 1 1 1 1 1 1 1 y = 0 0 0 0 0 0 0 0 1 1 0 0 0 0 0 0 1 1 1 0 0 0 0 0 1 1 1 1 0 0 0 0 1 1 1 1 1 0 0 0 1 1 1 1 1 1 0 0 1 1 1 1 1 1 1 0 1 1 1 1 1 1 1 1 y = 0 0 0 0 0 0 0 0 1 0 0 0 0 0 0 0 1 1 1 0 0 0 0 0 1 1 1 1 0 0 0 0 1 1 1 1 1 0 0 0 1 1 1 1 1 1 0 0 1 1 1 1 1 1 1 0 1 1 1 1 1 1 1 1 y = 0 0 0 0 0 0 0 0 1 0 0 0 0 0 0 0 1 1 0 0 0 0 0 0 1 1 1 1 0 0 0 0 1 1 1 1 1 0 0 0 1 1 1 1 1 1 0 0 1 1 1 1 1 1 1 0 1 1 1 1 1 1 1 1 y = 0 0 0 0 0 0 0 0 1 0 0 0 0 0 0 0 1 1 0 0 0 0 0 0 1 1 1 0 0 0 0 0 1 1 1 1 1 0 0 0 1 1 1 1 1 1 0 0 1 1 1 1 1 1 1 0 1 1 1 1 1 1 1 1 y = 0 0 0 0 0 0 0 0 1 0 0 0 0 0 0 0 1 1 0 0 0 0 0 0 1 1 1 0 0 0 0 0 1 1 1 1 0 0 0 0 1 1 1 1 1 1 0 0 1 1 1 1 1 1 1 0 1 1 1 1 1 1 1 1 y = 0 0 0 0 0 0 0 0 1 0 0 0 0 0 0 0 1 1 0 0 0 0 0 0 1 1 1 0 0 0 0 0 1 1 1 1 0 0 0 0 1 1 1 1 1 0 0 0 1 1 1 1 1 1 1 0 1 1 1 1 1 1 1 1 y = 0 0 0 0 0 0 0 0 1 0 0 0 0 0 0 0 1 1 0 0 0 0 0 0 1 1 1 0 0 0 0 0 1 1 1 1 0 0 0 0 1 1 1 1 1 0 0 0 1 1 1 1 1 1 0 0 1 1 1 1 1 1 1 1 y = 0 0 0 0 0 0 0 0 1 0 0 0 0 0 0 0 1 1 0 0 0 0 0 0 1 1 1 0 0 0 0 0 1 1 1 1 0 0 0 0 1 1 1 1 1 0 0 0 1 1 1 1 1 1 0 0 1 1 1 1 1 1 1 0 y = 0

3   Pass
A = [-1 -3 -6; -6 0 -5; 1 2 5] y_correct = -6; assert(isequal(sumOfN(A),y_correct))

A = -1 -3 -6 -6 0 -5 1 2 5 y = -1 0 0 -6 0 0 1 2 5 y = 0 0 0 -6 0 0 1 2 5 y = 0 0 0 -6 0 0 1 2 5 y = 0 0 0 -6 0 0 1 2 0 y = -6

4   Pass
A = [-1 -3 -6; -6 0 -5; 1 2 -1] y_correct = -6; assert(isequal(sumOfN(A),y_correct))

A = -1 -3 -6 -6 0 -5 1 2 -1 y = -1 0 0 -6 0 0 1 2 -1 y = 0 0 0 -6 0 0 1 2 -1 y = 0 0 0 -6 0 0 1 2 -1 y = 0 0 0 -6 0 0 1 2 0 y = -6